Pengaruh Return on Investment (ROI) dan Net Profit Margin (NPM) terhadap Return Saham pada Perusahaan Perbankan Badan Usaha Milik Negara (BUMN) yang terdaftar dalam Indeks LQ45 periode 2020-2024 - Erviyanda, Viona; Prasetya, Bangun Putra (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effect of Return on Investment (ROI) and Net Profit Margin (NPM) on Stock Returns in State-Owned Enterprise (BUMN) Banking Companies listed in the LQ45 Index. The period in this study is 2020-2024. This research uses a quantitative approach. The population in this study were all banks listed in the LQ45 Index, using financial statement data of State-Owned Enterprises (BUMN) banking companies listed in the LQ45 Index for 2020-2024. The sample selection technique uses the purposive sampling method. The data analysis method used is multiple linear regression analysis. The results showed that Return on Investment (ROI) and Net Profit Margin (NPM) together had a significant effect on Stock Returns. The adjusted R-squared value is 0.680 or 68.0%. This shows that Return on Investment (ROI) and Net Profit Margin (NPM) affect Stock Returns by 68.0%, while the remaining 38.0% is explained by other variables outside the model.